2015
DOI: 10.1182/blood-2015-06-655043
|View full text |Cite
|
Sign up to set email alerts
|

From cytopenia to leukemia: the role of Gfi1 and Gfi1b in blood formation

Abstract: The DNA-binding zinc finger transcription factors Gfi1 and Gfi1b were discovered more than 20 years ago and are recognized today as major regulators of both early hematopoiesis and hematopoietic stem cells. Both proteins function as transcriptional repressors by recruiting histone-modifying enzymes to promoters and enhancers of target genes. The establishment of Gfi1 and Gfi1b reporter mice made it possible to visualize their cell type–specific expression and to understand their function in hematopoietic linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 84 publications
(110 reference statements)
6
81
0
Order By: Relevance
“…GFi1 and its paralog GFi1B are critical transcriptional regulators for proliferation and maturation of hematopoietic stem cells. [48][49][50] Although it is unclear whether GFi1/GFi1B plays a role in repressing g-globin transcription, our analysis provides evidence for a potential GFi1 regulatory sequence in the HbF silencing region.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…GFi1 and its paralog GFi1B are critical transcriptional regulators for proliferation and maturation of hematopoietic stem cells. [48][49][50] Although it is unclear whether GFi1/GFi1B plays a role in repressing g-globin transcription, our analysis provides evidence for a potential GFi1 regulatory sequence in the HbF silencing region.…”
mentioning
confidence: 75%
“…The formation of protein complexes between GFi1/GFi1B mediates histone modifications associated with gene transcription silencing and regulation of hematopoiesis. [48][49][50]81 Studies by Vassen and colleagues demonstrated increased transcription of the embryonic and fetal globin genes and delayed erythroid maturation in Gfi1B-null mice 82 providing evidence that GFi1/GFi1B are involved in murine globin gene regulation.…”
mentioning
confidence: 99%
“…GFI1B is a proto-oncogene and transcriptional regulator that with its paralog, GFI1, acts as a gene repressor during early hematopoietic stem cell development [22][23][24][25]. GFI1 primarily intervenes in myeloid and lymphoid generation and genetic variants cause neutropenia.…”
Section: Gfi1b Transcription Repressormentioning
confidence: 99%
“…We show the full-length GFI1B protein, a shorter splice form lacking ZNF2 and parts of ZNF1 and 3 may also be found in hematopoietic tissue. The mutations or non-synonymous SNPs identified by Chen et al [25] are in black and occur along the protein; the truncating mutations within exon 6 characterized by Stevenson et al [27] and by Monteferrario et al [28] and affecting ZNF5 and 6 are in red. [Color figure can be viewed in the online issue, which is available at wileyonlinelibrary.com.]…”
Section: Gfi1b Transcription Repressormentioning
confidence: 99%
“…Here it controls diverse developmental processes, such as cell fate determination, differentiation, proliferation and cell survival (for review, see (50)(51)(52)(53)(54)). Outside the hematopoietic system, Gfi1 mRNA has been detected in a wide range of other tissues, but expression of Gfi1 protein seems to be restricted to mechanoreceptors cells (hair cells and Merkel cells), neurons of the cerebellum and retina, and specialized epithelial cells in the gut and lung (Table 1).…”
Section: Gfi1 and The Gps Family Of Transcription Factorsmentioning
confidence: 99%